Odin's ways: a guide to the Pagan God in the medieval literature - Lassen, Annette (Routledge, Taylor & Francis Group, 2022)
The reception of Odin in research -- Excursus : the vocabulary of 'myth' in an Old Norse/Icelandic context -- Odin and the Roman gods in early Latin texts and Old Norse/Icelandic translations -- The ecclesiastical explanations of paganism -- Odin in various Old Norse/Icelandic genres -- Odin in the contemporary saga Sturlunga saga -- Odin in the courtly romances (riddarasögur) -- Odin in kings' sagas (konungasögur) -- Odin in the legendary sagas (fornaldarsögur Norðurlanda) -- Odin in Skaldic poetry -- Odin in the Gesta Danorum -- Odin in Ynglinga saga -- Odin in Snorri's Edda -- Odin in the Eddic poems.